Compromising and Repositioning the Meaning of Corruptors as Thieves in Applying the Provisions of Shara’ into the Modern Era Context - Helmina, Helmina; Harun, Hermanto; Witro, Doli; Ardi, Muh Zaitun; Busni, Darti (Universitas Islam Negeri Raden Intan Lampung, 2024)
The debates on the application of Islamic criminal law in various Muslim-majority countries are still ongoing. This is because these countries still adhere to a positive legal system. This phenomenon has spread to many things including implementing the punishment of cutting off the hands of corruptors as is the punishment for thieves in the provisions of Islamic criminal law. One of the obstacles, in this case, is due to differences of opinion on the use of the term